2015
DOI: 10.1055/s-0035-1545073
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Review of the Treatment Methodologies of Carotid Stenosis

Abstract: The treatment of carotid stenosis entails three methodologies, namely, medical management, carotid angioplasty and stenting (CAS), as well as carotid endarterectomy (CEA). The North American Symptomatic Carotid Endarterectomy Trial (NASCET) and European Carotid Surgery Trial (ECST) have shown that symptomatic carotid stenosis greater than 70% is best treated with CEA. In asymptomatic patients with carotid stenosis greater than 60%, CEA was more beneficial than treatment with aspirin alone according to the Asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
5
0
1
Order By: Relevance
“…CAS is initially caused by abnormal proliferation of vascular smooth muscle cells (VSMCs), accompanied by intimal hyperplasia caused by matrix deposition of extracellular connective tissue to form plaques and eventually develops into symptomatic stenosis ( 4 , 5 ). There are various measures to prevent or treat CAS, including endarterectomy, endovascular stent placement ( 6 ) and medication ( 7 ). However, prophylactic surgery for CAS is controversial for patients with asymptomatic CAS ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…CAS is initially caused by abnormal proliferation of vascular smooth muscle cells (VSMCs), accompanied by intimal hyperplasia caused by matrix deposition of extracellular connective tissue to form plaques and eventually develops into symptomatic stenosis ( 4 , 5 ). There are various measures to prevent or treat CAS, including endarterectomy, endovascular stent placement ( 6 ) and medication ( 7 ). However, prophylactic surgery for CAS is controversial for patients with asymptomatic CAS ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…6 -9 While low dose aspirin (81-325 mg/day) is recommended after carotid surgery, the role of dual antiplatelet therapy (DAPT) remains less clear. 5,10 -14…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] While low dose aspirin (81-325 mg/day) is recommended after carotid surgery, the role of dual antiplatelet therapy (DAPT) remains less clear. 5,[10][11][12][13][14] Carotid restenosis following endarterectomy has been reported in up to 20% of cases, with more recent studies reporting rates of less than 10%. 1,[15][16][17][18] While some studies have found reduced stoke rates when clopidogrel and aspirin are administered in combination, these results have not been reproduced in larger studies and have yet to be tested in a randomized trial.…”
Section: Introductionmentioning
confidence: 99%
“…Several preventive measures have been developed to treat carotid artery stenosis, such as surgical plaque removal by carotid endarterectomy (CEA), endovascular stent placement, 26,28 and/or pharmacological treatment. 2 Nevertheless, the surgical management of asymptomatic patients with ≥ 70% carotid artery stenosis and < 10 years of life expectancy is highly controversial due to the improvement of the medical treatment. 13,25 The degree of carotid artery stenosis and plaque neovascularization, evaluated through imaging techniques such as contrast-enhanced ultrasound, positron emission tomography/computed tomography (PET/CT), and MRI, is being considered a most important predictor of carotid plaque vulnerability and, consequently, of increased risk of stroke in patients with carotid artery disease.…”
mentioning
confidence: 99%